Consumer Decision in Determining the Purchase of Products Based on The Offer Price - Nur Aida Azzahra; Noneng R Sukatmadiredja (INCOME: Innovation of Economics and Management, 2023)
Customer behavior is closely related to purchasing decisions, and individuals, groups, and groups make purchasing decisions to meet their needs and aspirations for products and services. Therefore, companies need to understand how consumers make purchasing decisions to influence their purchasing decisions. This article reviews the factors that affect consumer purchases, namely consumer decisions, prices, and products, and is a literature study of consumer behavior. This article aims to build a hypothesis of influence between variables to be used in future research. The results of this literature review article are as follows: 1) Promotion affects Consumer Purchases; 2) Price affects Consumer Purchases; and 3) Products that affect Consumer Purchases.